Developmental Coordination Disorder under the light of Inclusive Education and Human Rights (Research, Society and Development, 2020)
The objective of this article is to conduct a theoretical reflection on the Developmental Coordination Disorder (DCD) from the perspective of Inclusive Education, arising from a qualitative literary review with the primary contribution of Brazilian Educational Legislation in the light of Human Rights. We approach the stages of identification of this disorder in children and adolescents, its influence on school life activities as well as the importance of the school's role, the perception of teachers in the recognition of this phenomenon and its attendance, in order to reduce school difficulties. The methodology is a bibliographic review. Our results draw the reader's attention to the prevalence of DCD, to the high rates of students with indicative of this disorder at the international, national and Amazonian levels, as well as the neglect of the special educational needs of students with this type of disorder. It is necessary for this public to be perceived, identified and recognized, since the inclusion of students with DCD is much more than a school issue, it is a matter of Human Rights.